Implementasi Data Mining Dalam Memprediksi Jumlah Pinjaman Dengan Algoritma C4.5 Pada Kopdit CU Damai Sejahtera - Sri Devi Manullang; Efori Buulolo; Ikhwan Lubis (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
The development of information technology now allows storing data in a very large time. This development has added to various fields, including credit facilities, so that the use of information technology in public institutions. Data mining is an activity that includes gathering the use of historical data to find the regularity of patterns, or relationships in large data. The process of predicting the number of customer loans so far in the savings and loan cooperatives is still based on looking directly at the loan amount of the customers and seeing the general ledger records in the cooperative. The application of the C4.5 algorithm is a case-solving solution that is often used in problem solving on classification techniques that have characteristics namely by the process of determining the entropy value and gain value from the possibility that each criterion is a reference decision followed by the process of the decision tree